Can biometrics beat the developing world's challenges?. (November 2016) - Storisteanu, Daniel M.L.; Norman, Toby L.; Grigore, Alexandra; Labrique, Alain B.
Abstract : The World Bank estimates that as many as 1.5bn people worldwide do not officially exist. This lack of formal identification is a key challenge across the developing world – without reliable, unique and persistent identifiers, governments and development organisations struggle to provide essential goods and services to the populations they serve. The problem is wide-ranging: the dynamic nature of subsistence or agricultural communities and largely dysfunctional civil registration systems, combined with rapid population growth, have led to communities which are uncountable and poorly censused. Paper-based identity systems are resource-intensive, fragile and easily manipulated.